Fuzzy Convexity Under cr-Order with Control Operator and Fractional Inequalities - Qi Liu; Muhammad Zakria Javed; Muhammad Uzair Awan; Loredana Ciurdariu; Badr S. Alkahtani (Fractal and Fractional)
This study is organized to introduce the concept of center–radius <semantics>(cr)</semantics>-ordered fuzzy number-valued convex mappings. Based on this class of mappings, we have initiated the idea of fuzzy number-valued extended <semantics>cr</semantics>-ℏ convex mappings incorporating control mapping ℏ. Furthermore, several potential new classes of convexity will be provided to discuss its generic nature. Also, some essential properties, criteria, and detailed characterizations through Jensen’s and Hermite–Hadamard-like inequalities are provided, incorporating Riemann–Liouville fractional operators, which are defined by <semantics>ρ</semantics>-level mappings. To validate the proposed fractional bounds through simulations, we consider both triangular and trapezoidal fuzzy numbers. Our results are based on totally ordered fuzzy-valued mappings, which are new and generic. The under-consideration class also includes a blend of new classes of convexity, which are controlled by non-negative mapping ℏ. In previous studies, the researchers have focused on different partially ordered relations.